Peningkatan Aktivitas Belajar PPKn melalui Pendekatan Pembelajaran SAVI pada Siswa Kelas III SD Negeri 2 Cakranegara - Dwiwahyuni, Peni (Lembaga Yasin AlSys, 2022)
The aims of this study were to find out: 1) To find out the SAVI learning approach can improve Civics learning activities in third grade students of SD Negeri 2 Cakranegara in the 2019/2020 academic year; 2) To find out the SAVI learning approach can improve Civics learning outcomes in third grade students of SD Negeri 2 Cakranegara for the 2019/2020 academic year. This research is a Classroom Action Research (CAR), using two cycles through the stages of planning, implementing action, observing, and reflecting. The subjects in this study were third grade students in the 2021/2022 academic year with a total of 27 students, consisting of 15 male students and 12 female students. The results of this study indicate that the increase in student activity in Civics learning using the SAVI approach in class III SD Negeri 2 Cakranegara during cycle I to cycle II has increased. In the first cycle, the score of the improvement of students in learning is 66.67. In the implementation of the second cycle the score increased by 91.67, an increase of 25 points. The increase in teacher activity in implementing Civics learning using the SAVI approach in class III SD Negeri 2 Cakranegara during the implementation of cycle I to cycle II continued to increase. In the first cycle the teacher's ability to carry out learning is 73.68%. In the second cycle the teacher's ability to carry out learning increased by 100%. In the second cycle the teacher's ability to carry out learning increased by 26.37 points. Increasing student learning outcomes obtained the average PPKn learning outcomes from the initial conditions to the second cycle continued to increase. That the average student learning outcomes in the initial conditions was 74.33%. In the first cycle, it increased by 5.97 points to 80.30%. Then in the second cycle the average student learning outcomes increased by 19.70 points to 100%.